Kajian Stilistika Pada Cerpen “Penari Dari Kutai” Dalam Kumpulan Cerpen Dunia Sukab Karya Seno Gumira Ajidarma - Annisa Zulfa Hasanah (Universitas Palan, 2023)
The meaning of a literary work depends on the use of its stylistic. The use of language style is intended to give a certain effect to a literary work, especially short stories. The object of research used was the short story 'Dancer from Kutai' by Seno Gumira Ajidarma. The purpose of this study is to elaborate the style, meaning and function used in short stories. This study used qualitative descriptive method. In the lexical aspect, the types of words, speech, nouns and verbs are more dominant. In the grammatical aspect, declarative sentences and interrogative sentences often appear. In the rhetorical aspect, there is a perception and imagery